Building Early Social and Emotional Relationships with Infants and Toddlers Integrating Research and Practice (Springer International Publishing, 2018)
This book provides a comprehensive overview of the process of building healthy early social and emotional relationships with infants from a developmental perspective. The book synthesizes current research on the contextual influences of attachment, family relationships, and caregiving practices on social-emotional development. Chapters examine the processes of socioemotional development-particularly in relationships with parents, other family members, and peers-and identify areas for promoting healthy attachments and resilience, improving caregiving skills, and intervening in traumatic and stressful situations. Chapters also present empirically-supported intervention and prevention programs focused on building early relationships from birth through three years of age. The book concludes with future directions for supporting infant mental health and its vital importance as a component of research, clinical and educational practice, and child and family policy. Topics featured in this book include: The effect of prenatal and neonatal attachment on social and emotional development. The impact of primary relationships and early experiences in toddlerhood. Toddler autonomy and peer awareness in the context of families and child care. Supporting early social and emotional relationships through The Legacy for ChildrenTM Intervention. How to build early relationship programming across various cultures. Building Early Social and Emotional Relationships with Infants and Toddlers is a must-have reference for researchers, clinicians and professionals, and graduate students in the fields of infant mental health, developmental psychology, pediatrics, public health, family studies, and early childhood education.